2018
DOI: 10.1021/acs.macromol.8b00003
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Controlled Interactions between Poly(N-isopropylacrylamide) Mesoglobules Probed by Fluorescence

Abstract: The temperature-dependent behavior of aqueous solutions composed of a small amount of monodisperse poly(N-isopropylacrylamide) (PNIPAM) labeled at one or both ends with pyrene (Pyn-PNIPAM with n = 1 or 2) and a 10-fold excess of a non-fluorescent poly(Nisopropylacrylamide) (PNIPAM(22K), Mn = 22,000 g/mol) was characterized using steadystate (SSF) and time-resolved (TRF) fluorescence. Turbidimetry studies indicated that all samples exhibited two temperature-induced transitions: one at Tc, the cloud point of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…As it turns out, this range of SDS concentration corresponds to the regime where the excimer decays showed a rise time reflected by negative A E– / A E+ values in Figure C, indicative of excimer formation by diffusion. In contrast, the blue shift in excimer emission found for SDS concentrations smaller than the CMC reflected the existence of ground-state dimers, as has been reported in earlier reports , and as would be expected from the absence of rise time in the excimer decays. The much less pronounced blue shift observed for the excimer fluorescence spectra of 3.1 mg/L Py(6.7)-SNP in water suggested that the pyrene labels in the absence of Np(48)-SNP were more mobile and generated aggregates where the pyrene labels were better aligned to form an excimer.…”
Section: Results and Discussionsupporting
confidence: 83%
“…As it turns out, this range of SDS concentration corresponds to the regime where the excimer decays showed a rise time reflected by negative A E– / A E+ values in Figure C, indicative of excimer formation by diffusion. In contrast, the blue shift in excimer emission found for SDS concentrations smaller than the CMC reflected the existence of ground-state dimers, as has been reported in earlier reports , and as would be expected from the absence of rise time in the excimer decays. The much less pronounced blue shift observed for the excimer fluorescence spectra of 3.1 mg/L Py(6.7)-SNP in water suggested that the pyrene labels in the absence of Np(48)-SNP were more mobile and generated aggregates where the pyrene labels were better aligned to form an excimer.…”
Section: Results and Discussionsupporting
confidence: 83%
“…Aqueous solutions of poly­( N -isopropylacrylamide) (PNIPAM) exhibit the phase behavior of low critical solution temperature (LCST) with a sharp thermal response at a high temperature of about 32 °C. Hydrogen bonds between the −CONH– group and the surrounding water molecules play the key role for the LCST behavior in the aqueous solution of PNIPAM. Okada and Tanaka proposed the pearl-necklace chain model together with the cooperative hydration concept, which has been successfully applied to theoretically derive the “very flat” LCST phase boundary of PNIPAM/H 2 O. For a given PNIPAM chain, the majority of the −CONH– groups are hydrated with the cooperative H-bonded water molecules to form the necklace part; whereas some dehydrated segments will develop the hydrophobic pearls along the necklace.…”
Section: Introductionmentioning
confidence: 99%